Effect of Cnidoscolus Aconitifolius on Some Biochemical Parameters in Wistar Rats Orally Exposed to Bonny Light Crude Oil - Onuoha, S.C.; Chukwuma , C.C; Okari, K.A. (International Journal of Health Sciences, 2023)
Purpose: Crude oil is used in folklore medicine to treat various forms of diseases and in most cases in combination with medicinal plants. Studies have reported that Cnidoscolus aconitifolius possess medicinal properties. The present study investigated the effect of different concentration of Bonny light crude oil and Cnidoscolus aconitifolius on some biochemical parameters of Wistar rats. The rats were orally exposed to different concentrations of Bonny light crude oil and Cnidoscolus aconitifolius leaf extract individually and in combination. Methodology: After an exposure period of 21days, the results revealed that Bonny light crude oil and the leaf extract at concentrations of 250 and 500mgkg-1b.wt can induce damage to the liver and kidney within 21days of consecutive administration. This is shown in results of histological analysis gotten from the liver and kidney tissues. Findings: This study revealed that the induction of the leaf extract of Cnidoscolus aconitifolius and Bonny light crude oil at concentrations of 250 and 500mgkg-1b.wt for 21days may affect the liver and kidney. Contributions to theory, policy and practice:Therefore, it is recommended that the use of this leaf extract and Bonny light crude oil at concentrations similar to the ones used in this study should be discontinued.